ELECTRONIC TRANSPORT IN GAN NANOWIRES - Chen, Jie (My University, 2010)
Gallium nitride nanowires (GaNNws) have attracted more and more attention among researchers due to their excellent performance to be the candidate of next generation semiconductor devices. Their characteristics are wide bandgap, high mobility, and high thermal stability. They have been employed in several emerging nanoscale devices, such as the light emitting diodes [1], high-speed field-effect transistors [2], lasers [3], and nanogenerators basing on the piezoelectric property [4]. GaN can crystallize in wurtzite and zinc-blende polytypes, but wurtzite is the more thermodynamically stable one and thus the only polytype considered in this work.